Awareness, knowledge and practices about mosquito borne diseases in patients of tertiary care hospital in Navi Mumbai - Wasnik, Sumit; Mehta, Arjun (International Journal Of Community Medicine And Public Health, 2017)
Background: Mosquito borne diseases are a serious public health concern in India. The incidence of Mosquito borne diseases is linked with economic and social development of the community. The objectives of the study were to assess the awareness, knowledge and practices about mosquito borne diseases in study population and explore the various myths about mosquito borne diseases among them. Methods: It is a hospital based cross-sectional study and the study participants will be patients getting admitted for any reason and having fever, in the general medicine male and female ward. This study period was 3 month (January to March 2017). Results: Total 150 patients admitted in male and female medicine ward were included in the study out of them 84 were male and 66 were female patients. It was observed that educated participants had more knowledge about mosquitoes borne diseases. Conclusions: Most of the participants didn’t know that clean water could be a source of breeding of mosquitoes. Many myths are prevalent in the study population about mosquitoes borne diseases.